Post-Keynesian vignettes on secular stagnation: From labor suppression to natural growth - Codrina Rada; Marcio Santetti; Ansel Schiavone; Rudiger von Arnim (The University of Utah, Department of Economics, 2021)
The stylized facts of neoliberalism include a decline in steady state rate of growth and labor share. Recent classical-Keynesian literature sees the latter as a cause for the former. A crucial element is the distinction between short and long run. The business cycle is profit-led and profit-squeeze, but the steady state features a wage led natural rate of growth. This paper presents simple macroeconomic models in this vein. Our starting point is to assume an adverse shock to real wage bargaining, which across all models depresses the labor share. We consider (i) a two-dimensional model in income-capital ratio and labor share, a (ii) three-dimensional model that adds the employment rate as state variable, and a (iii) four-dimensional model that furthermore endogenizes the savings propensity. Key results are that model (i) predicts an increase (decrease) in the warranted (natural) rate of growth, and thus does not generate balanced growth; (ii) resolves this problem and predicts stagnation in steady state, but implies a long run paradox of thrift; and (iii) allows for contextualization vis-à-vis the utilization controversy.
Keywords: E12; E25; E32; J50; 330; Goodwin theory; labor suppression; secular stagnation